Deletion of nicotinamide nucleotide transhydrogenase: a new quantitive trait locus accounting for glucose intolerance in C57BL/6J mice. - Freeman, H; Hugill, A; Dear, N; Ashcroft, F; Cox, R (2006)
The C57BL/6J mouse displays glucose intolerance and reduced insulin secretion. The genetic locus underlying this phenotype was mapped to nicotinamide nucleotide transhydrogenase (Nnt) on mouse chromosome 13, a nuclear-encoded mitochondrial protein involved in beta-cell mitochondrial metabolism. C57BL/6J mice have a naturally occurring in-frame five-exon deletion in Nnt that removes exons 7-11. This results in a complete absence of Nnt protein in these mice. We show that transgenic expression of the entire Nnt gene in C57BL/6J mice rescues their impaired insulin secretion and glucose-intolerant phenotype. This study provides direct evidence that Nnt deficiency results in defective insulin secretion and inappropriate glucose homeostasis in male C57BL/6J mice.